2021
DOI: 10.1155/2021/2170788
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Model for Anomaly Detection in Network Traffic Based on Support Vector Machine and Clustering

Abstract: New vulnerabilities and ever-evolving network attacks pose great threats to today’s cyberspace security. Anomaly detection in network traffic is a promising and effective technique to enhance network security. In addition to traditional statistical analysis and rule-based detection techniques, machine learning models are introduced for intelligent detection of abnormal traffic data. In this paper, a novel model named SVM-C is proposed for the anomaly detection in network traffic. The URLs in the network traffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Through the experiment, these previous work confirmed that their classifier was better than other existing ML-based classifiers while saving computational costs [13].…”
Section: Ddos Detection With ML Model In Wired Networkmentioning
confidence: 58%
See 3 more Smart Citations
“…Through the experiment, these previous work confirmed that their classifier was better than other existing ML-based classifiers while saving computational costs [13].…”
Section: Ddos Detection With ML Model In Wired Networkmentioning
confidence: 58%
“…Ma et al [13] proposed an optimization model that adjusts the hyperparameters of Gaussian kernel SVM for anomaly detection in network traffic. The experiment was conducted with benign/malicious binary classification (for three datasets), which showed an accuracy of 99.98%.…”
Section: Ddos Detection With ML Model In Wired Networkmentioning
confidence: 99%
See 2 more Smart Citations